Być obywatelem - rozważania na temat rozwoju polskiego społeczeństwa obywatelskiego - Żurowska-Berkowicz, Aleksandra (Wydawnictwo Naukowe UAM, 2014)
The article discusses the concept of civil society. The author briefly elaborates on how this concept developed and enumerates the factors that determine its condition. The problem of social incapability of civil behaviour in public life continues to be an issue. The author points to the era of socialism and transformation processes as the causes of the current situation. A very important part in raising children and youngsters as future citizens is played, among others, by schools. Formally, this happens by means of implementing civil education. Various initiatives are launched nationwide and across Europe to promote civil education and prepare individuals for the role of active citizens in democratic societies. Do Polish citizens know their rights and responsibilities? Do they engage in any forms of civil activity? Are they aware of the mechanisms that are at work in civil societies? This article attempts to answer the question of what it means to be a citizen nowadays.
Keywords: civil education; citizen; democracy; Polish civil society